Correlations Of Reading Motivation and Engagement of Parents Towards Reading Comprehension Attainment: A Survey Research At SMA 3 Pangkalpinang - Rasuan, Zulfikri B (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
This study examines the correlations between students' reading attitudes, reading motivation, parental involvement, and reading comprehension achievement. Using a quantitative research method, data were collected from 150 randomly selected eleventh-grade students (77 males, 73 females) at SMA N 3 Pangkalpinang during the 2019-2020 academic year. Questionnaires measured reading attitudes, motivation, parental involvement, and education, alongside a reading comprehension test. Results revealed a significant correlation between reading motivation and comprehension (r = 0.424). Extrinsic motivation showed a moderate correlation (r = 0.599, p < 0.001), while intrinsic motivation exhibited a low correlation (r = 0.399, p = 0.016). Findings suggest that extrinsic motivation has a stronger influence on reading comprehension than intrinsic motivation, with parental involvement also playing a role. Therefore, it answered the research that there was a relationship between reading motivation and Engagement of Parents Towards Reading Comprehension. For the details, the correlation of intrinsic motivation and reading comprehension is significant in 0,016 by the coefficient correlation 0,399 that considered as low correlation. In another side, the correlation of extrinsic motivation and reading comprehension is significant in 0,000 by the coefficient correlation 0,599 that considered as moderate correlation. It can be concluded that based on the data that was analyzed, the students reading extrinsic motivation influence the students‟ comprehension more than the intrinsic motivation. In other words, the contribution of reading motivation towards reading comprehension was not strongly significant for the second-year students of SMA N 3 Pangkalpinang